Conflits Armés Et Fragilité De L’autorité Étatique Au Nord-Kivu En République Démocratique Du Congo - Bahama, Tabin Lissendja (European Scientific Journal, ESJ, 2017)
This article analyzes the official institutional weakness of Congo’s state in its quest to strengthen its authority in the province of North Kivu. Indeed, since 1998, it became obvious that state authority at both the central and provincial levels in the Democratic Republic of the Congo (DRC) were weakened by armed groups’ activism, war-based economy, borders’ looseness, militarization of local economy, and its extraversion. The most obvious challenge today is that private actors and organizations are acting in networks and mobilizing strategies. These strategies were employed in order to prevent the expansion of state authority over their areas of intervention. The presence of the latter would heavily affect the emergence and the pursuit of business, often associated with illicit practices. The operatory mode of this predation considerably limits Congo’s state capacity and it was to the detriment of the local population. This study revealed that Congo’s state is no longer capable of redeploying its authority in the province of North Kivu. On the other hand, it does not want to do it anymore because this state of chaos paradoxically protects the political and economic interests of certain members of the ruling class. Its apparent weakness denotes more unwillingness than a real incapacity.